Investment Intentions Among Students in Bali Province - Dewi, Luh Gede Kusuma; Wahyuni, Made Arie; Dewi, Nyoman Ayu Wulan Trisna (Akuntansi: Jurnal Akuntansi Integratif, 2023)
During the Covid-19 pandemic, social media was filled with cryptocurrency investment, however the results of research in 2022 showed that only 17% of respondents were interested in investing in cryptocurrency. Therefore, this research was carried out again to determine the investment intentions of students in Bali Province. The results of this research found that currently, students have invested in savings, deposits, shares, gold, mutual funds and other types of investment. The conclusions that can be drawn are: students fully understand Access information about investments. Investment concepts. types of investment. Benefits from investment. ways to invest. investment instruments. However, there are still students who do not understand the basic knowledge of managing finances. the importance of financial planning in investment decisions. Investment for low income. Therefore, there is a need for further socialization regarding investment through formal channels such as schools or lectures and also non-formal channels such as social media.